Pengaruh Kadar Etanol Darah Terhadap Kadar Gamma Glutamyl Transferase (GGT) pada Pekerja Pembuatan Etanol di Desa Ngombakan Polokarto: The Effect of Blood Ethanol on Gamma GT Levels in Ethanol Manufacturer Workers in Ngombakan Polokarto - Santi Santi; Wimpy Wimpy (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
Ethanol is the result of sugarcane fermentation which is converted into molasses (cane drops). Then the distillation process is carried out by heating for a certain time so that a certain level of ethanol is obtained. The process of making ethanol is an activity that has a high risk for its workers. The heating process produces vapors that are harmful to the body, causing health problems for workers. Liver disease is the most common complication caused by exposure to ethanol. Alcoholic fatty liver is a reversible disease that can progress to alcoholic hepatitis which can cause liver cirrhosis and liver failure. This study was conducted to determine blood ethanol levels, Gamma GT levels and the effect of blood ethanol levels on Gamma GT in ethanol production workers. The research was conducted by quota sampling as many as 24 people in 8 traditional ethanol-making industrial houses in Ngombakan, Polokarto. Ethanol examination was carried out using the Gass Chromatography and Mass Spectrometry method and Gamma GT was carried out using the colorimetric enzymatic method. The results obtained are the average ethanol content of the workers is 0.45 mg/dL and Gamma GT is 29 U/L. The results of linear regression analysis showed Sig. 0.257 (0.05) meaning that there was no effect of ethanol content on Gamma GT levels. Based on the coefficient of determination (R2) of 0.058, it means that the effect of ethanol on Gamma GT is 5.8%.